Towards biobanking technologies for natural and bioengineered multicellular placental constructs - Pogozhykh, Olena; Prokopyuk, Volodymyr; Prokopyuk, Olga; Kuleshova, Larisa; Goltsev, Anatoliy; Figueiredo, Constanca; Pogozhykh, Denys (Biomaterials. 2018 Dec;185:39-50., 2018)
Clinical application of a large variety of biomaterials is limited by the imperfections in storage technology. Perspective approaches utilizing low-temperature storage are especially challenging for multicellular structures, such as tissues, organs, and bioengineered constructs. Placenta, as a temporary organ, is a widely available unique biological material, being among the most promising sources of various cells and tissues for clinical and experimental use in regenerative medicine and tissue engineering. The aim of this study was to analyse the mechanisms of cryoinjuries in different placental tissues and bioengineered constructs as well as to support the viability after low temperature storage, which would contribute to development of efficient biobanking technologies. This study shows that specificity of cryodamage depends on the structure of the studied object, intercellular bonds, as well as interaction of its components with cryoprotective agents. Remarkably, it was possible to efficiently isolate cells after thawing from all of the studied tissues. While the outcome was lower in comparison to the native non-frozen samples, the phenotype and expression levels of pluripotency genes remained unaffected. Further progress in eliminating of recrystallization processes during thawing would significantly improve biobanking technologies for multicellular constructs and tissues.
Pogozhykh O, Prokopyuk V, Prokopyuk O, Kuleshova L, Goltsev A, Figueiredo C, Pogozhykh D. Towards biobanking technologies for natural and bioengineered multicellular placental constructs. Biomaterials. 2018 Dec;185:39-50. doi: 10.1016/j.biomaterials.2018.08.060. Epub 2018 Sep 7. PMID: 30218835.
Keywords: placental tissues; amniotic membrane; alginate microspheres; bioengineered constructs; multipotent stromal cells; biobanking